Efektifitas Model Problem Based Learning Berbantuan Lembar Kerja Siswa Untuk Meningkatkan Kemampuan Literasi Numerasi Ditinjau Dari Rasa Ingin Tahu Siswa Sekolah Dasar - Firmansyah, Firmansyah; Siregar, Nahrun Najib; Purwati, Purwati; Haryanto, Haryanto (Elementary Teacher Education Program, Majalengka University, 2023)
Literacy skills mark the quality of human resources in a country. However, Indonesia's performance in literacy assessment on an international scale has not been very good. The results of interviews with teachers of SD Inpres 18 subsay Manokwari district on March 14, 2022 found the fact that students' numeracy literacy skills were still very low. This study aims to test the effectiveness of the problem-based learning model assisted by student worksheets to improve numeracy literacy skills in terms of the curiosity of elementary school students in Manokwari district. The approach used in the implementation of this research is a quantitative approach. This type of research is experimental research. Data collection techniques in this study are Numeration literacy test, Observation, Validation Sheet and Documentation. Data analysis includes data analysis of validity and effectiveness. The effectiveness data analysis includes the completeness test for numeracy literacy skills, the average difference test for numeracy literacy skills, testing the effect of curiosity character on numeracy literacy skills. The results of the Effectiveness Test Analysis show that problem based learning models assisted by student worksheets are effective in improving numeracy literacy skills by criteria: (1) The proportion of classical learning completeness can be said to be more than 75% of students getting a score of 65, (2) The numeracy literacy ability of students in classes that use problem based learning models assisted by student worksheets is better than students' numeracy literacy skills with conventional learning, (3) There is an effect of curiosity character (X) on posttest numeracy literacy ability (Y).